Peningkatan Perilaku Perawatan Kaki Melalui Edukasi Booklet Smart untuk Pencegahan Diabetic Food Ulcer pada Pasien Diabetes Melitus Tipe 2 - Laila Revalina Madu; Ita Sulistiani Basir; Sitti Fatimah M. Arsad (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effectiveness of the SMART Booklet educational media on foot care behavior in type 2 diabetes mellitus patients at the Limboto Community Health Center. The method used was a pre-experimental design with a one-group pre-test post-test design. The results showed an increase in foot care behavior after the intervention with a p-value of 0.000 (p < 0.05), indicating a significant difference before and after education. In conclusion, education using the SMART Booklet effectively improved foot care behavior in type 2 diabetes mellitus patients.   Keywords: SMART Booklet, Diabetic Foot Ulcer, Foot Care Behavior